2009
DOI: 10.1161/circulationaha.108.833491
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Improves Survival After Cardiac Arrest and Cardiopulmonary Resuscitation via a Nitric Oxide Synthase 3–Dependent Mechanism in Mice

Abstract: Background— Sudden cardiac arrest (CA) is one of the leading causes of death worldwide. We sought to evaluate the impact of hydrogen sulfide (H 2 S) on the outcome after CA and cardiopulmonary resuscitation (CPR) in mouse. Methods and Results— Mice were subjected to 8 minutes of normothermic CA and resuscitated with chest compression and mechanical ventilation. Seven minutes after the onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
153
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 189 publications
(161 citation statements)
references
References 30 publications
6
153
1
1
Order By: Relevance
“…Hemodynamic studies using a pressure-volume conductance catheter (34) revealed that the PHD inhibitor did not ameliorate the cardiac dysfunction in mice with MALA ( Fig. 3 and data not shown), indicating that the rescue effect of a PHD inhibitor on MALA is independent of cardiac function.…”
Section: Discussionmentioning
confidence: 94%
“…Hemodynamic studies using a pressure-volume conductance catheter (34) revealed that the PHD inhibitor did not ameliorate the cardiac dysfunction in mice with MALA ( Fig. 3 and data not shown), indicating that the rescue effect of a PHD inhibitor on MALA is independent of cardiac function.…”
Section: Discussionmentioning
confidence: 94%
“…Further investigation is needed to study the mechanism by which CaMKK␤ is stimulated by hydrogen sulfide. Hydrogen sulfide induction of AMPK phosphorylation has also been described in the brain in a rodent model of cardiac arrest (57).…”
Section: Discussionmentioning
confidence: 94%
“…Mice were anesthetized with isoflurane at 16 h after CLP and ventilated with a rodent ventilator (Harvard Apparatus, Holliston, MA) via tracheal intubation. To evaluate LV function, the LV apex was exposed via a thoracotomy, and a 1.4-Fr pressure-volume catheter (SPR 839; Millar Instruments, Houston, TX) was inserted through the apex to lie along the longitudinal axis (Minamishima et al, 2009). To ensure proper placement, pressurevolume tracings were evaluated in real time to adjust the catheter as necessary.…”
Section: Farnesyltransferase Inhibitor Protects Mice Against Sepsis 833mentioning
confidence: 99%